Analisis Kesalahan Siswa SMP Berdasarkan Newman dalam Menyelesaikan Soal Kemampuan Berpikir Kritis Matematis pada Materi Bangun Ruang Sisi Datar - Iwan Darmawan; Anis Kharismawati; Heris Hendriana; Ratni Purwasih (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
This study used a qualitative approach and the type of research conducted is descriptive. Taking the subjects of this study were 33 students of class IX SMP Negeri 16 Bandung academic year 2017/2018. Based on the results of data analysis shows that no students can answer correctly all the questions that have been given. Based on data analysis, it can be concluded that reading error 13.0%, comprehension 3.7%, transformation 12.2%, skill 9.7%, writing final answer 16.3% and carelessness 7.7%, errors done by students include: Newman's procedure is reading errors, comprehension errors, transformation errors, process skills errors, and errors in encoding errors and careless errors. The cause factor is not able to compose the meaning of the word thought into the form of a sentence matamatika, not understand the questions asked, less thorough, less able to capture information problems contained in the problem, forgot, lack of practice working on various story form problems.